The Role of Education Operating Costs Against the Output on Madrasah Aliyah in Indonesia - Muhammad Imad (Indonesian Journal of Islamic Studies, 2018)
The purpose of this study was to determine the role of fishers’ operational costs on the output of education in Madrasah Aliyah in Cimahi. This research uses descriptive study method because the problems studied are actual and factual so that researchers are able to study intensively about the background of the present situation. In this study, the authors used several data collection techniques, namely observation, interviews and documentation studies. In this study, there were 2 Aliyah Madrasas which became the object of the sample to be used as a comparison so that the researchers knew the role of educational operational costs on educational output namely Madrasah Aliyah Mutiteknik Asih Putera and Madrasah Aliyah Al-Farisy. Whereas the output of education in this study is seen from the value of the average NEM of Student Exams from each school. From various data obtained by the author about elite objects, the results of the study indicate that the role of educational operational costs in this study has an influence on educational output. This means that the high average operational costs of education result in better outputs of education.